Factors influencing habitat choice of bird species: a comparison of a natural and an artificial wetland - Kolozsvári István; Коложварі Степан; Szerényi Szilárd; Серені Сілард; Molnár Ferenc; Молнар Федір; Kohut Erzsébet; Kohut Erzsebet; Когут Ержебет (Національний науково-природничий музей НАН України, 2022)
Abstract. Between 2019 and 2022, we studied the avifauna and environmental conditions of two wetland habitats located in close proximity to each other in Transcarpathia (nearby to the village of Dyida, Zakarpatska Oblast, Ukraine) — one being a natural, currently protected but drying and highly degraded former bog (Tóvár Ornithological Reserve), whereas the other one being an artificial pit lake (Lake Dyida). Lake Dyida is used as recreation area during the summer nesting season of birds. Both of these wetlands border with agricultural lands. Bird species that occur in both of the investigated habitats are affected by severe anthropogenic disturbances. A total of 27 795 individuals of 58 bird species were observed in the two areas over the four study years. Results indicate that the species composition of the two study sites differed considerably, both on annual and seasonal basis. Seasonal precipitation totals strongly influence the current spatial ratios of terrestrial and waterbird species, and show a strong positive correlation with the seasonal total number of bird species. Maximum numbers of birds are recorded in spring and summer at Tóvár and in autumn and winter at Lake Dyida. In the case of Lake Dyida, these could partly be due to the autumn–winter appearance of migratory waterbirds and the end of the beach season. Despite the impact of numer ous anthropogenic factors and habitat distrubances, the natural wetland is much more speciesrich even in its degraded condition than the artificial wetland, which has been confirmed not only for bird species but also for plant species in the two areas. Duck species consider the deepwater pit lake as an alternative habitat during periods of drought, but for waders the great water depth makes this site less exploitable. In Europe, too, drying out due to seasonal precipitation shortages is an issue of increasing concern, especially for wetlands beacuse artificially maintained lakes and reservoirs cannot fully take over the role of natural lakes, marshes and bogs, which will have severe consequences in the future.

Резюме. У період з 2019 по 2022 рр. нами досліджено орнітофауну та природні умови двох розташованих поруч водноболотних угідь Закарпаття (c. Дийда, Україна), одне з яких — висихаюче, сильно деградоване, колишнє болото природного походження, яке зараз перебуває під охороною (Орнітологічний заказник «Тóвар»), а друге — штучно створене кар’єрне озеро (озеро Дийда). У літній сезон озеро Дийда використовується як зона відпочинку. Обидва водноболотні угіддя межують із сільськогосподарськими угіддями. Обидва досліджені ділянки перебувають під значним антропогеннім впливом. За чотири роки досліджень у цих двох оселищах спостережено 27 795 екз. 58 видів. Показано, що видовий склад птахів двох територій суттєво відрізняється у різні роки та різні сезони. Сезонна кількість опадів значною мірою впливає на актуальне просторове співвідношення наземних і водних видів птахів та демонструє сильну позитивну кореляцію із сезонною загальною кількістю видів птахів. Максимальна кількість особин навесні та влітку спостерігається на озері Тóвар, а восени та взимку — на озері Дийда. У випадку з озером Дийда — це, ймовірно, частково є наслідком осінньозимової появи мігруючих водоплавних птахів і закінчення пляжного сезону. Разом із багатьма антропогенними факторами порушення середовища існування, оселище природного походження, навіть у його деградованому стані, має набагато вищий показник видового багатства порівняно зі штучно стовреним оселищем. Це підтверджено не тільки кількістю видів птахів, але й видів рослин обох територій. У періоди посухи глибоководне кар’єрне озеро розглядається представниками родини качкових як альтернативне оселище, проте воно є менш привабливим для куликів через велику глибину води. Висихання внаслідок періодичної відсутності опадів стає дедалі серйознішою проблемою і в Європі, особливо для водноболотних угідь, оскільки, озера і водосховища, що підтримуються штучним водозаміщенням, не можуть повністю взяти на себе роль природних озер та боліт, що матиме серйозні наслідки у майбутньому.
Фактори, які впливають на вибір оселища видами птахів: порівняння природного та штучного водно-болотного угіддя
Keywords: waterbirds; terrestrial birds; wetland; drying out; Transcarpathia